Sebaceous carcinoma: evidence-based clinical practice guidelines. Issue 12 (December 2019) - Owen, Joshua L; Kibbi, Nour; Worley, Brandon; Kelm, Ryan C; Wang, Jordan V; Barker, Christopher A; Behshad, Ramona; Bichakjian, Christopher K; Bolotin, Diana; Bordeaux, Jeremy S; Bradshaw, Scott H; Cartee, Todd V; et al.
Summary: Sebaceous carcinoma usually occurs in adults older than 60 years, on the eyelid, head and neck, and trunk. In this Review, we present clinical care recommendations for sebaceous carcinoma, which were developed as a result of an expert panel evaluation of the findings of a systematic review. Key conclusions were drawn and recommendations made for diagnosis, first-line treatment, radiotherapy, and post-treatment care. For diagnosis, we concluded that deep biopsy is often required; furthermore, differential diagnoses that mimic the condition can be excluded with special histological stains. For treatment, the recommended first-line therapy is surgical removal, followed by margin assessment of the peripheral and deep tissue edges; conjunctival mapping biopsies can facilitate surgical planning. Radiotherapy can be considered for cases with nerve or lymph node involvement, and as the primary treatment in patients who are ineligible for surgery. Post-treatment clinical examination should occur every 6 months for at least 3 years. No specific systemic therapies for advanced disease can be recommended, but targeted therapies and immunotherapies are being developed.